Changing sea level, changing shorelines: integration of remote-sensing observations at the Terschelling barrier island - B. Aschenneller; R. Rietbroek; D. van der Wal; D. van der Wal (Natural Hazards and Earth System Sciences)
Sea level rise is associated with increased coastal erosion and inundation. However, the effects of sea level change on the shoreline can be enhanced or counteracted by vertical land motion and morphological processes. Therefore, knowledge about the individual contributions of sea level change, vertical land motion and morphodynamics on shoreline changes is necessary to make informed choices for climate change adaptation, such as applying coastal defence measures. Here, we assess the potential of remote-sensing techniques to detect a geometrical relationship between sea level rise and shoreline retreat for a case study at the Terschelling barrier island at the northern Dutch coast. First, we find that sea level observations from satellite radar altimetry retracked with ALES can represent sea level variations between 2002 and 2022 at the shoreline when the region to extract altimetry time series is chosen carefully. Second, results for cross-shore time series of satellite-derived shorelines extracted from optical remote-sensing images can change considerably, depending on choices made for tidal correction and parameter settings during the computation of time series. While absolute shoreline positions can differ on average by more than 200 m, the average trend differences are below 1 m yr−1. Third, by intersecting the 1992 land elevation with time-variable sea level, we find that inundation through sea level rise caused on average −0.3 m yr−1 of shoreline retreat between 1992 and 2022. The actual shoreline movement in this period was on average between −2.8 and −3.2 m yr−1, leading to the interpretation that the larger part of shoreline changes at Terschelling is driven by morphodynamics. We conclude that the combination of sea level from radar altimetry, satellite-derived shorelines and land elevation provides valuable information about the influence of sea level rise, vertical land motion and morphodynamics on shoreline movements.